1 - Annonce du diagnostic et rupture biographique - Tinsa Francine (African Sociological Review, 2010)
The paper refers to the « grounded theory » (théorisation ancrée) targeting an indepth exploration of the announcement of the diagnosis as one of the first compo- nents of the trajectory of cancer. We considered first the theory of the contexts aware- ness, formulated in 1965 by Strauss and Glaser. The contexts of the announcement of diagnosis have been identified as major categories through an inductive analysis within the empiric phase. They have been built based on different announcement strategies recorded during the observation of the practitioners’ intentions, on expectations expressed by patients in term of information, on specific conditions around the actions. The key in- formants (n= 21) are patients having cancer and hospitalized for chemotherapy. Other lo- cal informants (clinical oncologists, volunteers, parents and closers, hospital cadres…)have contribute to the data collection. The aim is to address the practitioners’ motivations and the meaning they give to the step of the announcement of the diagnosis. We also aim at recontextualizing that step according to the tutoring planned by the normative instance. The paper analyses specific conditions linked to the organizational contexts that slow the scope of opening. We are wondering about the impact of such lack of opening and introduction to the disease as well as about the next steps of each therapeutic itinerary.